Full-inorganic Sb2(S, Se)3 solar cells using carbon as both hole selection material and electrode. (10th November 2018) - Wang, Weihuang; Chen, Guilin; Wang, Zhezhe; Wang, Ke; Chen, Shuiyuan; Huang, Zhigao; Wang, Xiaomin; Chen, Tao; Zhu, Changfei; Kong, Xiangkai
Abstract: Sb2 (S, Se)3 are considered as a promising absorber material for solar cells owing to its earth-abundant, nontoxic constituent, simple phase and long-term durability. In this work, a facile chemical bath deposition followed by post-selenization was introduced to prepare Sb2 (S, Se)3 thin film, which leads to a graded band gap structure. The sulfoselenide Sb2 (S, Se)3 thin films with smooth morphology were obtained through optimizing the selenization process. Meanwhile, a low cost and substitutable carbon electrode was used as hole selection material. Sequentially, the full-inorganic Sb2 (S, Se)3 device with efficiency of 2.64% was also fabricated according to structure of FTO/CdS/Sb2 (S, Se)3 /Carbon, which is the highest value in CBD processed FTO/CdS/Sb2 (S, Se)3 /Carbon solar cells. Graphical abstract: Highlights: Full in-organic Sb2 (S, Se)3 device is fabricated by CBD route followed post-selenization. A gradient band gap in Sb2 (S, Se)3 device is formed and exhibits efficiency of 2.64% with Voc of 645mV. The development of the crystal structure and morphology with increasing temperature was investigated carefully. The characteristics of the Sb2(S, Se)3 device were fully investigated.